(3JPcQI GdabgGAs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s ((3eMeO Hf QajY Hf eMeO GdCUagGfi s)
(3ChdgG (B:s
(3GdbUO GdKGfi ai GdQgf hajg ebOeg haUhd CeG GdebOeI aajgG HMKGf s
(3BNQgG (B:s
(3jhUi HeGd GdjJje aEf cGf GdeMGd Ydjg Gedi ef GdChd s
(3HgG fXGe GdJYbjHIs
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B303s
Keywords: (3abg GdePGgH GdCNQis